A faster strongly polynomial time algorithm to solve the minimum cost tension problem - Ghiyasvand, Mehdi (Journal of combinatorial optimization, 2017)
This paper presents a strongly polynomial time algorithm for the minimum cost tension problem, which runs in O ( max { m 3 n , m 2 log n ( m + n log n ) } ) time, where n and m denote the number of nodes and number of arcs, respectively. Our algorithm improves upon the previous strongly polynomial time of O ( n 4 m 3 log n ) due to Hadjiat and Maurras (Discret Math 165(166):377–394, 1997 ).